ORANG TUA SEBAGAI BASIS PENDIDIKAN AKHLAK ANAK SEJAK DINI - Idhar Idhar (FASHLUNA, 2022)
This paper is a literature study using a descriptive qualitative approach, aiming to reveal the role of parents as the basis for children's moral education from an early age. The results of this study reveal that the morals of parents are the morals of the children themselves, the meaning of these words teaches parents that children can be good, moral, virtuous and have noble character, if true parents are able to build a human spirit, love saying between peers, it means that parents have changed or educated their children with good morals. Therefore, human moral education does not seem like returning the palms of the hands, but it takes patience and fortitude from the parents themselves. We can see the moral education of children from an early age from the participation of parents or it can be seen or reflected in the activities of parents in the household how parents are kind to their husbands and wives, to neighbors, to the children themselves. So indeed the types of parents vary in educating children, some are relaxed and give freedom to children according to character, there are parents in educating children selfishly as if children are objects that must be regulated and parents are the first teachers for children. their children in terms of being responsible for the moral education of children from an early age. Children's moral education is reflected in the attitudes and roles of parents in domestic life, starting from how parents speak kind words, do good between a pair of fathers and mothers at home, it will affect the character growth of a child.